Bio-Functional Sperm Parameters: Does Age Matter? - Condorelli, Rosita A.; La Vignera, Sandro; Barbagallo, Federica; Alamo, Angela; Mongioì, Laura M.; Cannarella, Rossella; Aversa, Antonio; Calogero, Aldo E. (Frontiers in Endocrinology, 2020)
The evaluation of biofunctional sperm parameters can explain some cases of idiopathic male infertility. Among these, sperm DNA fragmentation (fDNA) is the most studied biofunctional sperm parameter. Mitochondrial membrane potential (MMP) correlates positively with sperm motility, the evaluation of sperm apoptosis by flow cytometry allows us to identify a population of spermatozoa not recognizable at the optical microscopy and finally, lipid peroxidation (LP) and mitochondrial superoxide levels measurements are rational oxidative stress indices. Male age seems to affect sperm concentration and sperm fDNA. For these reasons, this study was undertaken to evaluate the correlation, if any, between male age and biofunctional sperm parameters evaluating their possible impact on fDNA. To accomplish this, MMP, degree of chromatin compactness, sperm apoptosis/vitality, fDNA, LP, and mitochondrial superoxide levels were evaluated by flow cytometry in a cohort of 874 men. A significant negative correlation was found between age and the percentage of alive spermatozoa (r = -0.75, p < 0.05). The percentage of spermatozoa with low MMP (L-MMP) correlated positively with the percentage of spermatozoa with abnormal chromatin compactness (r = 0.24, p < 0.05). Spermatozoa with abnormal chromatin compactness and L-MMP correlated negatively with the percentage of alive spermatozoa (r = 0.83, p < 0.05) and positively with spermatozoa with PS externalization (r = 0.13, p < 0.01). The percentage of alive spermatozoa correlated negatively with both the percentage of spermatozoa with PS externalization (r = 0.24, p < 0.01) and of the spermatozoa with fDNA (r = 0.10, p < 0.05). Spermatozoa with PS externalization correlated positively with the percentage of spermatozoa with fDNA (r = 0.09, p < 0.05). Spermatozoa with LP correlated positively with the percentage of spermatozoa with increased mitochondrial superoxide (r = 0.11, p < 0.01) In conclusion, these findings in a large number of men suggest that age, mitochondrial damage, and alteration of chromatin compactness could activate the apoptotic cascade which could result in an increased fDNA rate.